Defining Romantic Self-Sabotage: A Thematic Analysis of Interviews With Practising Psychologists. (2019) - Peel, Raquel; Caltabiano, Nerina; Buckby, Beryl; McBain, Kerry
Abstract: The term 'self-sabotage' is not well defined in the current literature. Self-sabotage is generally explained as a synonym of self-handicapping, which does not fully encompass intrinsic behaviours found in romantic relationships. Therefore, the aim of the present study was to explore the theme of self-sabotage as viewed by practising psychologists. A series of 15 semistructured interviews with psychologists specialising in romantic relationships around Australia identified the main issues contributing to self-sabotage in romantic relationships and the reason why it might happen. Future studies will need to be conducted to develop a scale to empirically test self-sabotage in romantic relationships.